Listeria monocytogenes σA Is Sufficient to Survive Gallbladder Bile Exposure - Boonmee, Atsadang; Oliver, Haley F.; Chaturongakul, Soraya (Frontiers in Microbiology, 2019)
Listeria monocytogenes is a foodborne Gram-positive bacterium causing listeriosis in both animals and humans. It can persist and grow in various environments including conditions countered during saprophytic or intra-host lifestyles. Sigma (σ) subunit of RNA polymerase is a transcriptional factor responsible for guiding the core RNA polymerase and initiating gene expression under normal growth or physiological changes. In L. monocytogenes, there is one housekeeping sigma factor, σA, and four alternative sigma factors σB, σC, σH, and σL. Generally, σA directs expression of genes required for normal growth while alternative σ factors alter gene expression in response to specific conditions (e.g. stress). In this study, we aimed to determine the exclusive role of σA in L. monocytogenes by comparing a wild type strain with its isogenic mutant lacking genes encoding all alternative sigma factors (i.e., sigB, sigC, sigH, and sigL). We further investigated their survival abilities in 6% porcine bile (pH 8.2) mimicking gallbladder bile and their transcriptomics profiles in rich medium (i.e. BHI) and 1% porcine bile. Surprisingly, the results showed that survival abilities of wild type and ΔsigBΔsigCΔsigHΔsigL (or ΔsigBCHL) quadruple mutant strains in 6% bile were similar suggesting a compensatory role for σA. RNA-seq results revealed that bile stimulon of L. monocytogenes wild type contained 66 genes (43 and 23 genes were up- and down-regulated, respectively); however, only 29 genes (five up- and 24 down-regulated by bile) were differentially expressed in ΔsigBCHL. We have shown that bile exposure mediates increased transcription levels of dlt and ilv operons and decreased transcription levels of prfA and heat shock genes in wild type. Furthermore, we identified σA-dependent bile inducible genes that are involved in phosphotransferase systems, chaperones, and transporter systems; these genes appear to contribute to L. monocytogenes cellular homeostasis. As a result, σA seemingly plays a compensatory role in the absence of alternative sigma factors under bile exposure. Our data support that the bile stimulon is prone to facilitate resistance to bile prior to initiated infection.